2023
DOI: 10.1002/ijc.34691
|View full text |Cite
|
Sign up to set email alerts
|

Circulating white blood cell traits and colorectal cancer risk: A Mendelian randomisation study

Abstract: Observational studies have suggested a protective role for eosinophils in colorectal cancer (CRC) development and implicated neutrophils, but the causal relationships remain unclear. Here, we aimed to estimate the causal effect of circulating white blood cell (WBC) counts (N = ~550 000) for basophils, eosinophils, monocytes, lymphocytes and neutrophils on CRC risk (N = 52 775 cases and 45 940 controls) using Mendelian randomisation (MR). For comparison, we also examined this relationship using individual‐level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…A recent systematic review investigating the myeloid-derived immune suppressor cell (MDSCs) subtypes and the prognosis of non-small cell lung cancer (NSCLC) patients also showed evidence that patients with high monocytic MDSC levels in peripheral blood experienced a worse prognosis ( 26 ). Indeed, similar MR analysis has reported a protective causal effect of elevated levels of circulating lymphocyte counts on colorectal cancer risk, though in other cancers and not involving specific immune cell subsets ( 27 ). In another systematic review, it was found that the high CD8+ tumor-infiltrating lymphocytes (TILs) were significantly associated with better prognosis in pan-cancer patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent systematic review investigating the myeloid-derived immune suppressor cell (MDSCs) subtypes and the prognosis of non-small cell lung cancer (NSCLC) patients also showed evidence that patients with high monocytic MDSC levels in peripheral blood experienced a worse prognosis ( 26 ). Indeed, similar MR analysis has reported a protective causal effect of elevated levels of circulating lymphocyte counts on colorectal cancer risk, though in other cancers and not involving specific immune cell subsets ( 27 ). In another systematic review, it was found that the high CD8+ tumor-infiltrating lymphocytes (TILs) were significantly associated with better prognosis in pan-cancer patients treated with immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 85%
“…CD80 and CD86, two identified members of the B7 family proteins expressed on dendritic cells, B cells, and antigen-presenting cells, could bind to costimulatory molecules CD28 and CTLA4 and act as their ligands to provide second signals for efficient activation or inhibition of T cells ( 29 ). According to the literature, CTLA4 with a higher binding affinity to CD80 delivers inhibitory signals for activation of T lymphocytes and immune responses against malignant tumors ( 27 ). Findings from an observational study have shown that increased CTLA4 T cells were found in aggressive pediatric osteosarcoma patients ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that alterations in certain common indicators in the blood routine test might serve as causative factors in tumor development, with their irregularities potentially aiding in the identification of individuals at risk of cancer. For instance, in comparison to healthy control groups, patients diagnosed with colorectal cancer may exhibit elevated levels of eosinophils and lymphocytes [ 5 ]. The increase in elevated eosinophil and lymphocyte levels is directly correlated with a heightened susceptibility to colorectal cancer [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in comparison to healthy control groups, patients diagnosed with colorectal cancer may exhibit elevated levels of eosinophils and lymphocytes [ 5 ]. The increase in elevated eosinophil and lymphocyte levels is directly correlated with a heightened susceptibility to colorectal cancer [ 5 ]. Likewise, a rise in platelet count has been associated with an increased lung cancer risk [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Studies conducted within the UK Biobank have chiefly centered around individual cancer types, with one reporting an inverse association between AEC and lung adenocarcinoma, 11 and another investigating the association of blood cell traits and colorectal cancer risk, where they found a protective effect of higher eosinophil count, even adjusted for all other WBC subtypes. 12 Broader knowledge of the associations between eosinophil markers and additional specific cancer sites may help to elucidate the role of inflammation and immunity in cancer development. Therefore, we investigated AEC associations across a wide spectrum of cancer sites among participants of a large prospective cohort.…”
mentioning
confidence: 99%